Odpowiedzi

2010-03-18T22:20:38+01:00
A)
4x-8y-4z=4(x-4y-z)
6a-9b+12y=6(a-3b+6y)

17 3 17
2010-03-18T22:25:40+01:00
A)
4x-8y-4z=4(x-2y-z)
6a-9b+12y=3(2a-3b+4y)
12a² +8b-20=4(3a² +2b-5)
b)
5a² -15b+20c=5(a² -3b+4c)
30x +18y -6=6(5x+3y-1)
36a+12b-6=6(6a+2b-1)
c)
63m+54n-9=9(7m+6n-1)
3.5a+0.7b-14=0,7(5a+b-20)
24 4 24
2010-03-18T22:27:22+01:00
A) 4x-8y-4z= 4(z-2y-z)
6a-9b+12y=3(2a-3b+4y)
12a do kwadratu +8m-20= 4(3a do kwadratu+2m-5)
b) 5a do kwadratu-15b+20c= 5(a do kwadratu - 3b+4c)
30x+18y-6= 6(5x+3y-1)
36a+12b-6=6(6a+2b-1)
c) 63m+54n-9= 9(7m+6n-1)
3,5a+0,7b-14=0,7(0,5a+1b-20)
7 5 7